The phosphatase of regenerating liver-3 protein (PRL-3) promotes glioma cell invasiveness by interacting with β3 –tubulin. Issue 2 (1st February 2022) - Ge, Zhenying; Gu, Tingxuan; Zhang, Lingge; Fan, Qingfang; Ma, Li; Fang, Na
ABSTRACT: PRL-3 is a tyrosine phosphatase linked with tumor metastasis. It is detected high expression in different kinds of cancers, including colorectal, gastric, ovarian, and liver cancer. Its high expression is positively correlated with the progression of tumors and negatively with survivals of patients. However, the detailed mechanism underlying PRL-3 in tumor metastasis still remains unclear. In the present study, we found that PRL-3 is able to bind to β3-tubulin in pull-down and co-immunoprecipitation assays. Furthermore, overexpression of PRL-3 dephosphorylated β3-tubulin, a component of cytoskeleton, which plays critical role in cell shape formation and migration. Using cell wound healing and matrigel invasion assays, we found that PRL-3 could promote the migration and invasion of glioma cells. Taken together, our study revealed that PRL-3 may be involved in migration and invasion of glioma by dephosphorylating β3-tubulin. It is tempting to speculate that dephosphorylation of β3-tubulin by PRL-3 results in assembly of the cytoskeleton and facilitates cell migration and/or tumor metastasis.